PEMBINAAN SENI LUKIS WAYANG BEBER BAGI SISWA SMAN I COLOMADU KARANGANYAR - FP Sri Wuryani (Abdi Seni, 2016)
Culture is a product of human’s creative force, creation, intention,  and sense  in order to fulfil their needs and  physically as well as mentally prosperous  life. Besides, culture represents the realization of human thinking in completing their needs for life. For the reason, culture as a human product cannot survive longer (langgeng). Wayang beber is one of human products that cannot live longer (langgeng). Besides that, wayang beber is also one of performance media and as a media of ritual performance as well.  Therefore,  it is our duty to introduce and to conserve , as well as to guard it in order that it, wayang beber, doesn’t  extinct  especially for the next generation.  That is why the writer is urged to do the development of wayang beber painting  in SMAN I Colomadu, Karanganyar so that the young generation will be able to know more  about  local culture which is so great and must be guarded.Key words : wayang beber, ritual, culture, and local